Engaging Students in English Writing via Instagram: An Action Research on Digital Literacy in High School - Marpaung, Syafaruddin (English Journal Antartika, 2024)
This study investigates using Instagram to improve English writing skills and enhance digital literacy among high school students. Using Classroom Action Research (CAR) over three cycles, this mixed-methods study involved 34 11th-grade students from SMA Negeri 2 Kota Tanjungbalai. The research focused on assessing improvements in writing skills such as grammar, creativity, and vocabulary through Instagram-based tasks. Results indicated significant improvements in student writing, with average scores increasing from 60 in Cycle 1 to 80 in Cycle 3. Instagram fostered student engagement, encouraged creativity, and provided a collaborative platform for peer feedback, making the learning process more relevant and enjoyable for Generation Z students. The study concludes that Instagram effectively integrates writing instruction with digital literacy, offering an engaging alternative to traditional methods. Further research is recommended to explore the application of social media in different educational contexts.